2018
DOI: 10.1021/acs.jpcc.8b05658
|View full text |Cite
|
Sign up to set email alerts
|

Test of the Transferability of the Specific Reaction Parameter Functional for H2 + Cu(111) to D2 + Ag(111)

Abstract: The accurate description of the dissociative chemisorption of a molecule on a metal surface requires a chemically accurate description of the molecule–surface interaction. Previously, it was shown that the specific reaction parameter approach to density functional theory (SRP–DFT) enables accurate descriptions of the reaction of dihydrogen with metal surfaces in, for instance, H2 + Pt(111), H2 + Cu(111), and H2 + Cu(100). SRP–DFT likewise allowed a chemically accurate description of dissociation of methane on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(61 citation statements)
references
References 81 publications
1
60
0
Order By: Relevance
“…Figure 3 shows elbow plots of the MS-B86bl PES computed for four configurations in which H 2 is parallel to the Ag(111) surface. Table 5 shows the associated geometries and barrier heights, comparing to the previous values of the SRP48 PES, 46 which gave sticking probabilities that were shifted to higher incidence energies by 6.6–7.6 kJ/mol with respect to results of molecular beam experiments 45 (note that the SRP48 functional is an SRP functional for H 2 + Cu(111) 12 but not for H 2 + Ag(111) 46 ). The results for the MS-PBEl functional are given in Figure S3 and Table S3.…”
Section: Resultsmentioning
confidence: 98%
“…Figure 3 shows elbow plots of the MS-B86bl PES computed for four configurations in which H 2 is parallel to the Ag(111) surface. Table 5 shows the associated geometries and barrier heights, comparing to the previous values of the SRP48 PES, 46 which gave sticking probabilities that were shifted to higher incidence energies by 6.6–7.6 kJ/mol with respect to results of molecular beam experiments 45 (note that the SRP48 functional is an SRP functional for H 2 + Cu(111) 12 but not for H 2 + Ag(111) 46 ). The results for the MS-PBEl functional are given in Figure S3 and Table S3.…”
Section: Resultsmentioning
confidence: 98%
“…As discussed in Section 2.2, the first set of parameters was extracted from experiments on D 2 + Ru(0001), 37 and we call this parameter set SBG, where S stands for seeded beams, B stands for broad in translational energy, and G stands for Groot et al 37 The second set of parameters is derived from the D 2 + Pt(111) experiments of Cao et al, 17 and we call this parameter set SBC. The third set of parameters (PNH) was reported in ref (42) to describe experiments of Hodgson and co-workers on D 2 + Ag(111), 16 and in this, acronym P stands for pure D 2 beam, N stands for narrow beams, and H stands for Hodgson and co-workers. The last set of parameters (PNA) describes pure D 2 beam experiments on D 2 + Cu(111) using translationally narrow beams.…”
Section: Resultsmentioning
confidence: 99%
“…The third set of parameters is a set of ⟨ E ⟩, σ, and T n describing a set of experiments of Hodgson and co-workers on D 2 + Ag(111) 36 for which the expansion conditions were similar to the conditions prevalent in the experiments on D 2 + Pt(111) of the same group. 16 The parameters, which were collected in Table 1 of ref (42) can be used together with eqs 1, 2, 5–7, andto compute sticking probabilities for E i in the range 0.22–0.49 eV, with the results corresponding to T n in the range 970–2012 K. For similar E i , the parameters describe distributions that are symmetric in incidence energy and beams that are narrower in incidence energy than the beams described by parameter sets 1 and 2 (see Figure 2 of ref (42), comparing to Figure 1 of ref (37)).…”
Section: Experiments and Beam Parameters Used To Simulate The Experimmentioning
confidence: 99%
See 1 more Smart Citation
“…22 However, it was found that a slightly modified version of this functional which still correctly modelled H 2 dissociation on Cu(111) 25 does not give a chemically accurate description for D 2 dissociation on Ag(111). 26 It was suggested that this was due to the functional not including van der Waals correlation, which has been shown to be necessary previously for giving accurate descriptions of dissociation dynamics. 14,27 The transferability of an SRP functional amongst different metals of the same group (group 10) of the periodic table has been demonstrated for methane dissociation, where the same SRP functional gives a chemically accurate description for the reaction of methane on Ni(111), 21,23,28 Pt(111), 23 and Pt(211).…”
Section: Introductionmentioning
confidence: 99%